Upaya meningkatkan kemakmuran dan keadilan hukum bagi masyarakat Indonesia melalui perbaikan tata kelola - Eka Novita (Lembaga Administrasi Negara, 2017)
The existence of a BUMN is expected to be a development agency, precisely as a state instrument to meet certain development objectives, such as providing essential products for the state and society, stabilizing the prices of goods, absorbing labor, as contributors to state income through dividends, taxes, and others. Therefore, it is necessary to know the implementation of GCG principles referring to the Regulation of the Minister of SOE Number PER-01 / MBU / 2011 on the Implementation of Good Corporate Governance (GCG) in SOEs. SOEs have corporate social responsibility in the form of reducing the number of unemployed, reducing the number of poor and increasing economic growth. SOEs in producing high quality goods and / or services at affordable prices through the management and supervision of SOEs require the application of GCG principles.Keywords: Good Corporate Governance / GCG, SOE, social responsibility, economic growth